Detection of EGFR mutations in plasma circulating tumour DNA as a selection criterion for first-line gefitinib treatment in patients with advanced lung adenocarcinoma (BENEFIT): a phase 2, single-arm, multicentre clinical trial. Issue 9 (September 2018) - Wang, Zhijie; Cheng, Ying; An, Tongtong; Gao, Hongjun; Wang, Kai; Zhou, Qing; Hu, Yanping; Song, Yong; Ding, Cuimin; Peng, Feng; Liang, Li; Hu, Yi; et al.
Summary: Background: Detection of EGFR mutations in tumour tissue is the gold-standard approach to ascertain if a patient will benefit from treatment with an EGFR tyrosine kinase inhibitor. However, if tissue is scant, another strategy is to use circulating tumour DNA (ctDNA), but this method needs validation in clinical trials. We did a prospective clinical trial to assess ctDNA-based EGFR mutation detection as a selection criterion for patients with lung adenocarcinoma receiving gefitinib as first-line treatment. Methods: BENEFIT is a multicentre, single-arm, phase 2 clinical trial at 15 centres in China. Patients aged 18–75 years with stage IV metastatic lung adenocarcinoma and EGFR mutations detected in ctDNA were given oral gefitinib 250 mg once daily as first-line treatment. The primary endpoint was the proportion achieving an objective response. Secondary endpoints included median progression-free survival and safety. Next-generation sequencing (NGS) of a 168-gene panel was used for genetic analysis of baseline blood samples. The primary efficacy analysis was done by intention to treat in patients who had at least one post-baseline tumour assessment. The safety analysis was done in all patients who received at least one dose of study treatment. This trial is registered withClinicalTrials.gov, numberNCT02282267 . Findings: Between Dec 25, 2014, and Jan 16, 2016, 426 patients were screened for the trial, of whom 188 with EGFR mutations in ctDNA were enrolled and received gefitinib. 183 patients had one or more post-baseline tumour assessment and were included in the primary efficacy analysis. Median follow-up was 14·5 months (IQR 12·2–16·5). At the time of data cutoff (Jan 31, 2017), 152 patients had progressive disease or had died. The proportion achieving an objective response was 72·1% (95% CI 65·0–78·5). Median progression-free survival was 9·5 months (95% CI 9·07–11·04). Of 167 patients with available blood samples, 147 (88%) showed clearance of EGFR mutations in ctDNA at week 8, and median progression-free survival was longer for these patients than for the 20 patients whose EGFR mutations persisted at week 8 (11·0 months [95% CI 9·43–12·85] vs 2·1 months [1·81–3·65]; hazard ratio [HR] 0·14, 95% CI 0·08–0·23; p<0·0001). From baseline NGS data in 179 patients, we identified three subgroups of patients: those with EGFR mutations only (n=58), those with mutations in EGFR and tumour-suppressor genes (n=97), and those with mutations in EGFR and oncogenes (n=24). Corresponding median progression-free survival in these subgroups was 13·2 months (95% CI 11·5–15·0), 9·3 months (7·6–11·0), and 4·7 months (1·9–9·3), respectively ( EGFR mutations only vs mutations in EGFR and tumour-suppressor genes, HR 1·78, 95% CI 1·23–2·58; p=0·002; EGFR mutations only vs mutations in EGFR and oncogenes, 2·66, 1·58–4·49; p=0·0003). The most common grade 3 or 4 adverse events were hepatic function abnormalities (n=24). Serious adverse events were reported in 17 (9%) patients. No unexpected safety events for gefitinib were recorded. Interpretation: Detection of EGFR mutations in ctDNA is an effective method to identify patients who might benefit from first-line gefitinib treatment. Further analyses of dynamic alterations of EGFR mutations and accompanying gene aberrances could predict resistance to gefitinib. Funding: Guangdong Association of Clinical Trials, AstraZeneca, National Natural Sciences Foundation Key Programme, and National Key Research and Development Programme of China.